A unique urinary metabolomic signature for the detection of pancreatic ductal adenocarcinoma. Issue 6 (12th November 2020) - Sahni, Sumit; Pandya, Advait R.; Hadden, William J.; Nahm, Christopher B.; Maloney, Sarah; Cook, Victoria; Toft, James A.; Wilkinson‐White, Lorna; Gill, Anthony J.; Samra, Jaswinder S.; Dona, Anthony; Mittal, Anubhav
Abstract: Our study aimed to identify a urinary metabolite panel for the detection/diagnosis of pancreatic ductal adenocarcinoma (PDAC). PDAC continues to have poor survival outcomes. One of the major reasons for poor prognosis is the advanced stage of the disease at diagnosis. Hence, identification of a novel and cost‐effective biomarker signature for early detection/diagnosis of PDAC could lead to better survival outcomes. Untargeted metabolomics was employed to identify a novel metabolite‐based biomarker signature for PDAC diagnosis. Urinary metabolites from 92 PDAC patients (56 discovery cohort and 36 validation cohort) were compared with 56 healthy volunteers using 1 H nuclear magnetic resonance spectroscopy. Multivariate (partial‐least squares discriminate analysis) and univariate (Mann‐Whitney's U ‐test) analyses were performed to identify a metabolite panel which can be used to detect PDAC. The selected metabolites were further validated for their diagnostic potential using the area under the receiver operating characteristic (AUROC) curve. Statistical analysis identified a six‐metabolite panel (trigonelline, glycolate, hippurate, creatine, myoinositol and hydroxyacetone), which demonstrated high potential to diagnose PDAC, with AUROC of 0.933 and 0.864 in the discovery and validation cohort, respectively. Notably, the identified panel also demonstrated very high potential to diagnose early‐stage (I and II) PDAC patients with AUROC of 0.897. These results demonstrate that the selected metabolite signature could be used to detect PDAC and will pave the way for the development of a urinary test for detection/diagnosis of PDAC. What's new?: Although most cases of pancreatic ductal adenocarcinoma (PDAC) are diagnosed after metastasis, roughly 8 years elapse between the initial mutation and the development of metastasis, representing a potential screening window. The current lack of sensitive and inexpensive diagnostic tests for early PDAC makes population screening impractical. However, this study using 1 H nuclear magnetic resonance spectroscopy identifies a six‐metabolite panel (trigonelline, glycolate, hippurate, creatine, myoinositol and hydroxyacetone) that shows good sensitivity and specificity in both the discovery cohort and an independent validation cohort, demonstrating its potential for development into a clinically useful diagnostic test for PDAC.